A Phase 1 Randomized, Placebo-controlled, Observer-blinded Trial to Evaluate the Safety and Immunogenicity of Inactivated Streptococcus pneumoniae Whole-cell Vaccine in Adults. Issue 4 (April 2020) - Keech, Cheryl A.; Morrison, Royce; Anderson, Porter; Tate, Andrea; Flores, Jorge; Goldblatt, David; Briles, David; Hural, John; Malley, Richard; Alderson, Mark R.
Abstract : Background: Broadly protective pneumococcal vaccines that are affordable for low-resource countries are needed. Streptococcus pneumoniae whole cell vaccine (wSp) is an investigational vaccine that contains killed cells from a nonencapsulated strain of S. pneumoniae (SPn) with aluminum hydroxide adjuvant. Studies in mice demonstrated protection against nasopharyngeal carriage (T-cell-mediated) and invasive pneumococcal disease (antibody-mediated). The aim of this randomized, double-blind, placebo-controlled Phase 1 study was to assess safety, tolerability and immunogenicity of wSp in healthy adults. Methods: Forty-two participants were randomized into 3 dose cohorts to receive 0.1, 0.3, or 0.6 mg of wSp or saline intramuscularly. Participants received a 3-dose vaccination schedule spaced by 4-week intervals. Postvaccination assessments included solicited reactogenicity events through day 7, blood chemistry and hematology assessments at day 7, and adverse events (AEs) through day 84. Participants were monitored for serum antibody and peripheral blood mononuclear cell cytokine responses to pneumococcal antigens. A 6-month telephone follow-up was completed to assess for any additional AEs. Results: wSp was safe and well tolerated. Reactogenicity was acceptable and no untoward safety signals were observed. wSp elicited potentially clinically significant rises (defined arbitrarily as at least a 2-fold rise) in immunoglobulin G responses to multiple pneumococcal antigens, including pneumococcal surface protein A and pneumolysin. Functional antibody responses were observed with the highest dose of wSp (0.6 mg). Increases in T-cell cytokine responses, including interleukin 17A, were also seen among wSp vaccines. Conclusions: wSp was safe and well tolerated in healthy US adults, eliciting pneumococcal antigen-specific antibody and T-cell cytokine responses.